INVESTIGATING THE RELATION BETWEEN THE RELATIONAL CAPABILITY AND THE PERFORMANCE OF THE ALLIANCE PORTFOLIO IN THE SEGMENT OF BRAZILIAN PHARMACEUTICAL LABORATORIES - Ribeiro Cordeiro, Jessica; Bataglia, Walter (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
The objective of this work is to understand the procedural relation between the activities of alliance management, that is, the relational capability, and the performance of the alliance portfolio in the segment of human health laboratories in the Brazilian pharmaceutical industry. We used the strategy of four case studies of contractual strategic alliances in different enterprises through interviews with the managers responsible for the alliances. The interviews were transcript and analyzed by the technique of thematic content analysis with categories defined a priori. It was concluded that the relational capability and the prior experience with alliances reduce transaction costs and may generate an alliance portfolio performance that overwhelms coordination costs.